Auditory steady state response in hearing assessment in infants with cytomegalovirus - Daniela Polo C. Silva; Priscila Suman Lopez; Jair Cortez Montovani (Sociedade de Pediatria de São Paulo, 2013)
OBJECTIVE: To report an infant with congenital cytomegalovirus and progressive sensorineural hearing loss, who was assessed by three methods of hearing evaluation. CASE DESCRIPTION: In the first audiometry, at four months of age, the infant showed abnormal response in Otoacoustic Emissions and normal Auditory Brainstem Response (ABR), with electrophysiological threshold in 30dBnHL, in both ears. With six months of age, he showed bilateral absence of the ABR at 100dBnHL. The behavioral observational audiometry was impaired due to the delay in neuropsychomotor development. At eight months of age, he was submitted to Auditory Steady State Response (ASSR) and the thresholds were 50, 70, absent in 110 and in 100dB, respectively for 500, 1,000, 2,000 and 4,000Hz in the right ear, and 70, 90, 90 and absent in 100dB, respectively for 500, 1,000, 2,000 and 4,000Hz in the left ear. COMMENTS: In the first evaluation, the infant had abnormal Otoacoustic Emission and normal ABR, which became altered at six months of age. The hearing loss severity could be identified only by the ASSR, which allowed the best procedure for hearing aids adaptation. The case description highlights the importance of the hearing status follow-up for children with congenital cytomegalovirus.